2002
DOI: 10.1002/lsm.10035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of using a short‐pulsed erbium:YAG laser for intraoperative resurfacing of surgical wounds

Abstract: Given the time and resources necessary to perform an intraoperative resurfacing procedure on the wound edges, it may be more reasonable to withhold resurfacing procedures for those few cases that may require it postoperatively (patients with a history of poor healing, highly sebaceous areas, etc.). When good operative technique is used, most surgical wounds on the head and neck heal very well with excellent aesthetic outcomes without any additional intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The body of evidence on early laser intervention comprises less than 30 studies applying laser within 3 months after injury. Thirteen of these studies were randomized controlled trials [7,24,25]. Sixteen studies applied laser in the proliferation phase of wound healing (4-21 days post-injury), generally performed at the point of suture removal using PDL, NAFL, and AFL.…”
Section: Discussionmentioning
confidence: 99%
“…The body of evidence on early laser intervention comprises less than 30 studies applying laser within 3 months after injury. Thirteen of these studies were randomized controlled trials [7,24,25]. Sixteen studies applied laser in the proliferation phase of wound healing (4-21 days post-injury), generally performed at the point of suture removal using PDL, NAFL, and AFL.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the methodological quality revealed generally high risk of bias according to random sequence generation and allocation concealment. Four studies 16,25,30,33 provided a clear and adequate randomization procedure. None of the trials described allocation concealment.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…Rohrer applied full-ablative Er:YAG immediately after intracutaneous suturing and found at 3 months follow-up improvement in overall cosmetic appearance of scars from treated lesions compared to untreated, though not significant. 30 Capon introduced the laser-assisted skin healing (LASH) procedure and performed two split scar studies using an 810-nm diode laser immediately after skin closure on surgical scars. The first study 31 showed improvement on treated scar side after 12 months on overall appearance rating.…”
Section: Laser Intervention In the Inflammation Phasementioning
confidence: 99%
“…In recent years, 2 studies using ablative laser resurfacing of wounds at the time of closure have shown promising trends. 4,5 Ablative fractional resurfacing has been shown to quantitatively improve atrophic surgical and traumatic scars. 6 The improved safety profile of fractional carbon dioxide lasers vs their fully ablative counterparts and the ability to treat nonfacial sites makes them well suited for scar treatments.…”
Section: A Randomized Split-scar Study Of Intraoperative Treatment Ofmentioning
confidence: 99%